CME/CPD in the Indian Subcontinent: Proceedings from the 1st regional meeting of Global Alliance for Medical Education (GAME) in Mumbai, India. Issue 1 (1st January 2015) - Srivastava, Vaibhav; Sullivan, Lisa; Sanghvi, Shwetal
Abstract : In today's fast paced environment, continuing medical education (CME) and continuing professional development (CPD) play a pivotal role in enhancement of clinical practice and patient care. Getting updated with the latest trends and practices has gained utmost importance for today's healthcare professional, be he or she a family physician, a specialist or a super specialist. In addition, the increased awareness of different diseases among the masses due to exposure to information from the media and Internet makes it vital for the healthcare provider to be aware of the latest knowledge and trends so that patients may be provided with the highest quality of treatment. India today boasts of having the largest number of medical schools in the world with an annual student intake of over 50, 000 prospective medical professionals. CME in India is at a rudimentary stage in development, but definitely evolving at a rapid pace. Despite the best efforts of the major stakeholders, such as the Medical Council of India (MCI), medical societies, educational institutions and key opinion leaders (KOLs) in the field, the CME scenario in India fails to have a systematic and integrated approach to match international standards. There is a huge need gap because the legislation to make CME mandatory has made little progress. One of the many reasons is that each state in India has its own individual norms, and without a federal system there exists no national guideline for appropriate specialty learning that practising doctors require as part of CPD. There is an unmet need for the provision of the right CME for the right doctor group at the right time to create appropriate learning levels. Therefore CME providers in India need guidance to navigate through rough waters with a multi-modal unbiased approach to bring together the needs of the Indian doctors and the needs of the patient population on a common platform. This report summarises the presentations and discussions that took place during the first regional meeting of The Global Alliance for Medical Education (GAME) in India on 18 October 2014 in Mumbai. The predominant participants and panel members included representatives from the MCI, medical education institutions, pharmaceutical industries and private sector providers of CME programmes. The conference was organised with the aim of bringing all the major CME stakeholders from India and CME global experts under one roof to discuss the challenges and possible solutions for the expansion of CME/CPD in India. With this motive as the primary focus of the meeting, eminent speakers and panellists attempted to identify region-specific issues in implementing legal and regulatory frameworks for CME. The group of experts attempted to identify ways to implement standards of good practice, so that the Indian doctor could match his/her international peers. The role of industry and that of private medical education providers was also discussed at length given their major presence in the country.